Effect of Probiotic Lactobacillus Strains on Phagocytic Activity of Murine Macrophage Cells Infected by Aggregatibacter Actinomycetemcomitans - Norzawani, Jaffar; Huiwen, Lim (Penerbit Universiti Sultan Zainal Abidin, 2020)
Periodontal diseases are prevalent inflammatory diseases affecting the periodontium stimulated by an oral pathogen, Aggregatibacter actinomycetemcomitans. Recently, there is an increasing interest in utilizing probiotic as a bacteriotherapy treatment for oral diseases. Macrophages are innate immune cells that perform phagocytosis and synthesis various cytokines when they encounter foreign particles. The aim study is to determine the immunomodulation capacity of heat-killed probiotic Lactobacillus casei subsp. rhamnosus NBRC 3831 and L. casei NBRC 15883 on the activation of RAW 264.7 murine macrophages in phagocytic activity and cytokines secretion to counteract A. actinomycetemcomitans strain infection. In this study, we analyzed the effects of heatkilled L. casei subsp. rhamnosus NBRC 3831, and L. casei NBRC 15883 on the innate immune response. The activity was evaluated based on the viability of macrophages, cytokines secretion, and macrophages' phagocytic action. The introduction of probiotic lactobacilli significantly induced the phagocytic activity of macrophages as compared to A. actinomycetemcomitans strains Y4 and ATCC 29524. Whereby L. casei NBRC 15883 showed the highest (p < 0.01) phagocytic activity compared to other groups. Besides, there was lower macrophage death when co-incubated with two tested lactobacilli strains, which indicated that lactic acid bacteria had the potential to trigger macrophages proliferation. Interestingly, the number of viable macrophages that pre-activated by probiotic before the addition of A. actinomycetemcomitans was higher than the untreated group. Moreover, Lactobacillus sp. was found to promote and modulate the pro-inflammatory cytokines (IL-1β, IL-6, and IL-8) by murine macrophages against A. actinomycetemcomitans infection after 24 and 48 h incubation in a strain and dose-specific pattern. In conclusion, probiotic Lactobacillus induce the phagocytosis activity, macrophage cell proliferation, and the release of IL-1β, IL-6, and IL-8 cytokines to modulate the immune response. These findings might provide crucial information on the efficacy of probiotic Lactobacillus in developing a promising candidate against A. actinomycetemcomitans infections.